Medical Assessment Role in Addiction Case Verdict - Anisa, Nurul; Yuspin, Wardah (Soepra Jurnal Hukum Kesehatan, 2023)
The prevalence of drug abuse cases is increasing day by day. This is accompanied by the high number of cases of drug crime. In handling drug-related cases, a medical assessment is required from a psychiatrist or a doctor authorized to provide an assessment. This article uses a research method in the form of a literature study. From this literature study it was found that medical assessment can play a role in the judicial process, protect suspects and the environment, and can play a role in improving drug handling. In Indonesia, sanctions for narcotics cases have a two-way system, namely criminal sanctions and operational sanctions. Criminal sanctions are used to prevent abuse and illicit traffic of Narcotics and Narcotics or their ingredients and rehabilitation is a form of action-consequence of drug abuse. Based on the law, judges can decide or order drug addicts to undergo treatment and/or treatment. Through an integrated assessment, which involves the medical team and the legal team. Judgments are viewed from a legal and medical point of view, so that more and more decisions are starting to include not only criminal decisions, but are also accompanied by medical rehabilitation decisions for drug users.